Optical Coherence Tomography for the Diagnosis of Exercise-Related Acute Cardiovascular Events and Inconclusive Coronary Angiography. (22nd July 2020) - Mas-Lladó, Caterina; Maristany, Jaume; Gómez-Lara, Josep; Pascual, Marcos; Alameda, María del Mar; Gómez-Jaume, Alfredo; Peral-Disdier, Vicente
Abstract : Objectives . The aim of this study is to assess the utility of optical coherence tomography (OCT) in patients with exercise-related acute coronary syndrome (ACS) presenting with inconclusive angiographic findings. Background . Regular physical activity reduces the incidence of cardiovascular events. Nevertheless, the risk of ACS or sudden cardiac death (SCD) increases during sport. In adults older than 35 years, exercise-related ACS or SCD is associated with plaque rupture, but not infrequently patients present ambiguous angiographic findings. Methods . Between September 2015 and January 2020, patients admitted for ACS or SCD triggered by physical exertion and with coronary stenosis ≤50% were included in this prospective observational study. OCT was performed on the artery deemed to be responsible of the event. Results . Ten patients were enrolled, predominantly men (80%) of middle age (51 years old, IQR 41–63) with low cardiovascular risk burden. Cycling was the most frequent (50%) exercise-related trigger, 8 patients were regular sport practitioners, and 7 had the clinical event during strenuous exertion. Five patients presented with non-ST-elevation ACS, two with ST-elevation ACS, and three with SCD. Angiographic analysis showed nonsignificant stenosis in all patients (42% stenosis, IQR 36–46). OCT identified the etiology of the event in 9 patients (4 plaque erosion, 3 plaque rupture, 1 eruptive calcific nodule, and 1 coronary dissection). Treatment was adjusted according to OCT findings. Conclusions . OCT is a valuable technique to identify the etiology of exercise-related ACS or SCD in patients with nonobstructive coronary arteries and, as a result, may lead to a more specific treatment.